Day-to-Day Scheduling Travel Time Adjustment Behavior and Simulation. (30th April 2014) - Li, Hua-Min; Wang, David Z. W.; Huang, Hai-Jun; Yu, Xiao-Jun
Abstract : This paper proposes a modeling framework to study the day-to-day scheduling travel time adjustment behavior on the base of past experiences. Scheduling travel time is defined as the difference between the requested arrival time and the departure time. Mathematical equations are established to formulate every traveler's dynamic adjustment on his/her departure time. In the adjustment process, the last day's scheduling time is an essential component, while the numbers of late arrivals, punctual arrivals, and early arrivals in a previous day are used to reflect the past experiences. Simulation results are presented to illustrate the effectiveness of the proposed modeling framework.